Access to care and factors that impact access, patients as partners in care and changing roles of health providers - Kronenfeld, Jennie J. (Bingley, U.K. : Emerald, 2011)
This volume in the highly-regarded Research in the Sociology of Health Care series, deals with both macro-level system issues and micro-level issues involving access to care, factors that impact access, patients as partners in care and changing roles of health providers. It includes: examination of factors that impact access to care such as racial/ethnic, social, demographic and structural sources, discussion of changing patterns of care and changing patterns of interaction between patients and providers of care, and investigation of changing roles of health care providers within the health care delivery system. Key contributions focus on linkages to policy, population concerns and patients and/or providers of care as ways to meet health care needs of people both in the US and in other countries. This volume relates to issues of consumers of health care services, providers of such services and policy perspectives. It also raises issues of the availability of services, access to those services, quality of services and the role of government in services provision.
Systems of health-care delivery : sociological issues linked to health reform and roles of patients and providers / Jennie Jacobs Kronenfeld -- Insider knowledge and male nurses : how men become registered nurses / Karrie Ann Snyder -- The direct care worker : overcoming definitions by negation / Thomas R. Konrad -- Medical interpreting by bilingual staff whose primary role is not interpreting : contingencies influencing communication for dual-role interpreters / Mary-Rose Mueller, Stergios Roussos, Linda Hill, Nadia Salas, Veronica Villarreal, Nicole Baird, Melbourne Hovell -- Private rehabilitation clinics in a public, universal health-care system / Walter Schönfelder, Trond Bliksvær -- Emergent situations when older homebound women had fortuitous help and a typology of helpers who were involved / Eileen J. Porter, Melinda S. Markham, Edward L. Kinman, Lawrence H. Ganong -- Patients, trust, and patient participation : factors influencing whether patients want to be active health care participants / Scott V. Savage -- Health-care consumerism and access to health care : educating elders to improve both preventive and end-of-life care / Eva Kahana, Boaz Kahana, Loren Lovegreen, Jeffrey Kahana, Jane Brown, Diana Kulle -- Feminist centers negotiating medical authority in the 21st century : implications for feminist care and the U.S. women's health movement / Ayse Dayi -- A strange thing happened on the way to the market : privatization in Malaysia and its effects on the health-care system / Kai-Lit Phua, Simon Barraclough -- American health care : public opinion differences in the confidence, affordability, and need for reform / Rebecca L. Utz, Richard Nelson, Peter Dien -- Medicare knowledge and health service utilization among older adults / Noah J. Webster.
Print version record
Keywords: Health services accessibility; Medical policy; Health & Fitness -- Health Care Issues; Social Science -- Sociology -- General; Medical -- Health Care Delivery; Health systems & services; Sociology